Microclimate modification through shading and watering frequency treatments as efforts for ex situ conservation of pule pandak (Rauvolfia serpentina) - SAMANHUDI, SAMANHUDI; PURWANTO, EDI; SULANDJARI, SULANDJARI; SETIYANINGSIH, ARY (Asian Journal of Agriculture, 2017)
Samanhudi, Purwanto E, Sulandjari, Setiyaningsih A. 2017. Microclimate modification through shading and watering frequency treatments as efforts for ex situ conservation of pule pandak (Rauvolfia serpentina). Asian J Agric 1: 35-39. Pule pandak (Rauvolfia serpentina Benth) is one of the rare medicinal plants. Exploration of nature continues to be done to meet the needs of the drug. That is why proper cultivation technique for pule pandak is required, by giving appropriate shading level and watering frequency to the growth and yield of pule pandak. The research aimed to examine the effect of shading and watering frequency on the growth and yield of pule pandak. The study was conducted from February to July 2009 in BBP Mondromino, Pokoh Village, Wonogiri at 141 meters above sea level. The experimental Design used in this research was a Split Plot Design consisted two factors and three repetitions. The first factor (main plot) was shading level consisted of three levels: 55%, 65%, and 75%. The second factor (sub plot) was watering frequency consisted of three levels: once three days, once five days and once seven days. Data were subjected to analysis of variance, followed by post hoc test of Duncan Multiple Range Test at 5% level. The reserpine content was analyzed descriptively. The results showed that no interaction between shading level and watering frequency on all variables. The shading level caused no significant effect on growth and yield of pule pandak except the leaf area. Watering frequency caused no significant effect on growth and yield of pule pandak except the chlorophyll content. The results showed that plants treated with watering frequency of five-day interval produced the highest chlorophyll content. Plants treated with shading level of 65% and watering frequency once five days produced the highest reserpine content.